467 Stimulator of Interferon Genes Protein (STING) Agonist Incited Sustained Antitumor Immunity in Murine Models of Glioblastoma. (April 2023) - Huntoon, Kristin; Lee, DaeYong; Lu, Yifei; Jiang, Wen; Curran, Michael; Kim, Betty Y.S.
Abstract : INTRODUCTION: Introduction: Stimulator of interferon genes (STING) is an innate pattern recognition receptor natively localized to the endoplasmic reticulum that detects both exogenous and endogenous pathogenic or damage-associated cytosolic cyclic dinucleotides (CDNs), activating IRF3 (interferon regulatory factor 3), NF-κB (nuclear factor κB), and STAT6 (signal transducer and activator of transcription 6) signaling pathways to induce a potent type I interferon and proinflammatory cytokine responses. Activation of the STING pathway has been recognized as a critical component of the innate immune sensing of tumors that is required for optimal cytotoxic T-cell priming against tumor antigens. Recently a highly potent cyclic dinucleotide STING agonist, IACS-8803, showed robust activation of the STING pathway resulting in systemic anti-tumor response in the B16 murine model of melanoma. Additionally, the STING agonists have been shown to achieve robust tumor regression at both injected and distal lesions and are reported to facilitate generation of long-lived immunologic memory. METHODS: Methods: We established murine gliomas with stereotactic implantation of GL261, a murine glioma cell line. Mice were assessed with luciferase imaging to ensure baseline tumor size and then randomized into treatment arms (IgG, IACS-8803, CD47, PD-1 and combinations thereof). Treatment was initiated one week after the tumor implantation. RESULTS: Results: All mice that received IACS-8803 had no detectable luciferase activity. Tumor regression was additionally verified via MR Imaging. Utilization of IACS-8803 led to long-term tumor-free survival (p < 0.01). Re-challenge with GL261 tumors ensured long term memory was sustained with a single dose of agonist. CONCLUSIONS: Conclusion: Engaging the STING pathway may be an ideal targeting strategy for GBM. Ongoing studies are delineating the mechanisms of activating this pathway with specific attention being paid to reprogramming and education of innate immunity.